The challenges of implementing a joint interprofessional education program between a pharmacy college and an osteopathic medical college: A case study. (September 2021) - Huggins, Charnicia E.; Basu, Paramita; Senhaji-Tomza, Batoul; Warwick, Shelly; Anthony, M. Esquire
Abstract: This case study describes a joint pilot project to implement interprofessional education (IPE) between a United States college of osteopathic medicine and a college of pharmacy co-located on one campus. The pilot was intended to address the Interprofessional Education Collaborative (IPEC) domains and competencies and to serve as a first step and bridge toward future multidisciplinary endeavors. We describe the process of creating an IPE team, developing a workshop and gathering feedback. The key elements for a successful IPE program are identified as: administrative support, faculty engagement, and long-term planning. Challenges to effective implementation encountered were: scheduling conflicts, faculty engagement, and a specific IPE budget. The aim of this paper is to provide insights and share lessons learned regarding approaches taken to implement this IPE initiative. We advance the premise that while IPE is an essential foundation for preparing health professions students for interprofessional patient-centered practices, its implementation has many challenges.